Virus-sampling technologies in different environments - Nourmoradi, Heshmatollah (Environmental and Health Management of Novel Coronavirus Disease (COVID-19 ), 2021)
Exposure to pathogenic microorganisms, especially viruses, can lead to various diseases, allergies, and hospital infections. The application of sampling procedure is still a challenge to sample viruses from different environments such as air, water, wastewater, etc. However, there are many procedures such as filtration, impactor, impinger, cyclone, electrostatic separator, and MD-8 airscan that are applied for sampling and measuring viruses from air. Among conventional filters, the gelatin type can be readily dissolved in a liquid for molecular counting or cell culture without significant changes in virus tissue. Liquid impingers are the most frequent devices that are applied for the collection of viral aerosols. Also, many methods including precipitation, ultracentrifugation, electronegative membrane, and ultrafiltration have been used to prepare samples of food, wastewater, feces, urine, and surfaces. In many studies, the aforementioned methods have been employed to sample the coronaviruses such as SARS-CoV-2 in various environments. Also, various PCR procedures have been commonly used to identify the virus from the environmental samples.